Environmental Education Resources from Federal and State Agencies - Martha C. Monroe; Alison W. Bowers (EDIS)
Going on a field trip? Want a spiffy new poster? Looking for a guest speaker? Or do you just need to know more about wildland fire, endangered species, coastal management, or invasive exotics? Many agencies are available to provide information, share resources, support field trips, and contribute to your environmental education programming. This 8-page fact sheet explores federal and state agencies in Florida with major educational resources. Written by Martha C. Monroe and Alison W. Bowers and published by the UF Department of School of Forest Resources and Conservation, December 2012.